Active control of aircraft cabin noise - Dimino, Ignazio; Aliabadi, M. H. (Computational and experimental methods in structures, 2015)
Active Control of Aircraft Cabin Noise provides a bridge to fill the gap between robust control theory and practical applications of active noise control systems in aircraft cabin.